Genetic isolation within the malaria mosquito A nopheles melas - Kevin C. Deitz; Giri Athrey; Michael R. Reddy; Hans J. Overgaard; Abrahan Matias; Musa Jawara; Alessandra della Torre; Vincenzo Petrarca; João Pinto; Anthony E. Kiszewski; Pierre Kengne; Carlo Costantini; et al. (Molecular Ecology, 2012)
Anopheles melas is a brackish water–breeding member of the Anopheles gambiae complex that is distributed along the coast of West Africa and is a major malaria vector within its range. Because little is known about the population structure of this species, we analysed 15 microsatellite markers and 1161 bp of mt DNA in 11 A. melas populations collected throughout its range. Compared with its sibling species A. gambiae , A. melas populations have a high level of genetic differentiation between them, representing its patchy distribution due to its fragmented larval habitat that is associated with mangroves and salt marsh grass. Populations clustered into three distinct groups representing Western Africa, Southern Africa and Bioko Island populations that appear to be mostly isolated. Fixed differences in the mt DNA are present between all three clusters, and a Bayesian clustering analysis of the microsatellite data found no evidence for migration from mainland to Bioko Island populations, and little migration was evident between the Southern to the Western cluster. Surprisingly, mt DNA divergence between the three A. melas clusters is on par with levels of divergence between other species of the A. gambiae complex, and no support for monophyly was observed in a maximum‐likelihood phylogenetic analysis. Finally, an approximate Bayesian analysis of microsatellite data indicates that Bioko Island A. melas populations were connected to the mainland populations in the past, but became isolated, presumably when sea levels rose after the last glaciation period (≥10 000–11 000 bp ). This study has exposed species‐level genetic divergence within A. melas and also has implications for control of this malaria vector.